Impact of Air Pollutants (NO2 and CO) on the Incidence of ARI in Toddlers in Palangka Raya 2024: Retrospective Study - Djinu, Lentar Adityas; Suhartono, Eko; Noor, Meitria Syahadatina; Syauqiah, Isna; Rahman, Fauzi; Perdana, Muhammad Ricky (Lambung Mangkurat University, 2025)
Palangka Raya, as the capital city of Central Kalimantan, has unique environmental characteristics because it often experiences forest and land fires (karhutla) which result in an increase in air pollutants. This study aims to analyze the association between exposure to Nitrogen Dioxide (NO2) and Carbon Monoxide (CO) pollutants and the incidence of Acute Respiratory Tract Infection (ARI) in toddlers in Palangka Raya in 2024. This retrospective study was conducted in Palangka Raya City, with data on the incidence of ARI in toddlers obtained from the Palangka Raya City Health Office. Determination of NO2 and CO levels using the Google Earth Engine (GEE) platform that analyzes TROPOspheric Monitoring Instrument (TROPOMI) satellite data from the Sentinel-5 precursor. Geographic Information System (GIS) software was used to process spatial data and map layout. The relationship between CO and NO2 levels and ARI incidence was analyzed using linear regression tests, followed by multiple linear regression tests if there was a significant correlation. All statistical tests were conducted using a web-based platform. The conclusion of this study was that the linear regression test showed that NO2 levels only contributed 2.07% (p=0.6555) and CO contributed weakly (p=0.4981) to the incidence of ARI. This indicates that other factors are more dominant in causing ARI in Palangka Raya